Synthesis of Functionalized 9-Substituted Fluorene Derivatives via Boron Trifluoride Catalysed Reaction of Coplanar 9-(Phenylethynyl)-9H-fluoren-9-ols, Aryl Aminoamides and N-Bromosuccinimide - Athira, Mohanakumaran; Shanmugam, Ponnusamy (SynOpen, 2021)
A boron trifluoride catalysed reaction of coplanar 9-(phenylethynyl)-9H-fluoren-9-ols with various 2-aminobenzamides affords a number of highly functionalized, conjugated (Z)-2-((2-(9H-fluoren-9-ylidene)-1-phenylethylidene)amino) benzamides in excellent yield. The reaction in the presence of N-bromosuccinimide affords (E)-5-bromo-2-((2-bromo-2-(9H-fluoren-9-ylidene)-1-phenylethylidene)amino)benzamides in very good yields. The scope of the reaction is demonstrated by selecting N-aryl substituted 2-aminobenzamides and aminosulfonamides as reaction partners. The structures of representative compounds were established by single-crystal XRD analysis. Based on the structure of the products, a plausible mechanism via formation of allene carbocation intermediates is proposed.
Keywords: aryl aminoamides; propargylic alcohol; N-bromosuccinimide; BF3·OEt2; fluorene; allene